STRATEGI PENANGANAN PENGANGGURAN DALAM PERSPEKTIF SIYASAH SYAR’IYYAH: (Studi Dinas Tenaga Kerja Kabupaten Soppeng) - Rhismayanti,; Tenripadang, Andi; Laman, Ilham (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2024)
This study aims to find out how the reality of unemployment in Soppeng Regency is and to know the role of the Soppeng Regional Government in dealing with Unemployment in Soppeng Regency. The research method used in this study is field research through an empirical juridical research method and a syar'i method. The effects of this have a look at suggest that, the reality of unemployment that occurs in Soppeng Regency causes the unemployment rate to continue to increase due to uncertain macroeconomic conditions in the region, especially Soppeng so that companies cannot develop their business in Soppeng so that the labor recruitment process is not optimal. The role of the Department of Manpower in dealing with unemployment in Soppeng Regency is to increase the distribution of workforce placement by establishing work connectivity networks, expanding job opportunities, and training & labor productivity in an effort to reduce unemployment. The role of the Department of Manpower and Transmigration in the Siyasa Syar'iyyah, in this case the Siyasa Syar'iyyah is appropriate and does not conflict with the rules contained in the Siyasa Syar'iyyah. That the manpower service is equivalent to a state leader in the context of an Islamic State. Both have the same task, namely to realize the benefit of the people.